Subluxation of the crystalline lens: A no-ring approach - Rodrigues, Antonio Carlos Lottelli [UNESP]; Trivedi, Rupal H.; Wilson, M. Edward (SLACK, 2012)
Purpose: To report the surgical technique and outcomes of a no-ring approach to posterior chamber intraocular lens (IOL) implantation in children and young adults with subluxation of the crystalline lens. Methods: A three-piece 5.5-mm hydrophobic acrylic IOL was implanted in which the optic and one haptic were inside the capsular bag and the other haptic was in the ciliary sulcus. The implantations were done in 13 eyes of 10 patients with lens subluxation. One haptic was fixated in the ciliary sulcus by passing it through an operculum-shaped opening in the capsular bag edge, made between 2 and 3 clock hours, clockwise from the middle point of the subluxated area. Results: The mean age of the 10 patients was 12.61 ± 8.04 years and the mean follow-up was 21.38 ± 11.29 months. The mean preoperative and postoperative best-corrected visual acuity (BCVA) was 1.15 ± 0.58 and 0.37 ± 0.17 logarithm of the minimum angle of resolution, respectively, in 11 measured eyes. The postoperative BCVA was 20/40 or better in 4 eyes (36.36%), between 20/40 and 20/60 in 6 eyes (54.54%), and between 20/80 and 20/100 in 1 eye (9.09%). The BCVA improved in all eyes. Postoperative IOL decentration between 1.0 and 1.5 mm occurred in 3 of 13 eyes (23.08%). Conclusion: The results indicate that the no-ring technique allows centration of an IOL implanted into a subluxated capsular bag without using capsule tension rings. © SLACK Incorporated.
Keywords: adolescent; adult; algorithm; capsule opacification; capsulorhexis; child; clinical article; female; follow up; human; hydrophobicity; lens implantation; lens subluxation; male; operculum (brain); outcome assessment; posterior eye chamber; postoperative period; preoperative period; retrospective study; school child; surgical technique; visual acuity